Estudo Experimental da Secagem do Betão Celular - José Manuel Ferreira de Castro (1999)
There is a growing use of cellular concrete in the building construction, executed "in situ", used as form layers of flat roofs and filling layers over concrete slabs inside the buildings. Tha advantages of this material are its low density, an easy application and a low cost.The drying of the cellular concrete, especially in case of layers of a certain thickness, is very complex and long. The application of waterproofing systems or coverings (wood, linoleum, etc...) on not fully dried cellular concrete, has resulted in the occcurence of pathologies.At the Building Physics Laboratory of the Faculty of Engineering of the University of Porto, we have carried out an experimental study with the aim of measuring the drying process of cellular concrete, whether under laboratory or outdoor conditions. The measurement of the moisture content profiles of the tested material was performed by means of gamma-ray attenuation.In this work, we present the experimental results of this study and we give some practical recommendations of the hygrothermal implications of the use of this type of materials.Key words: Cellular concrete, moisture, drying, experimental study, gamma ray attenuation, pathology